De Magia (Ms. Laud Or. 282, Bodleian Library): edição e estudo - Alexia Teles Duchowny (2007)
This thesis consists of the edition and the study of the unedited manuscript De Magia (Ms. Laud Or. 282), kept in the Oriental Section of the Bodleian Library, in Oxford, England. De Magia is an astrological guide written in the first half of the fifteenth century and it is an aljamiado manuscript: the characters are in semicursive Hebrew and the language is Old Portuguese. The general goals of the thesis are to produce a semidiplomatic edition of De Magia and to make an analysis some characteristics of the aljamiado Old Portuguese. Emphasis has been given to the understanding of the graphemes bet, vet and vav, equivalent to <v> and of non-aljamiado Portuguese. In the Introduction, the objectives are presented and the edition of the manuscript and the analysis of bet, vet and vav are justified; in Chapter 1, the codicological and paleographic aspects of De Magia are detailed and the manuscript is dated; in Chapter 2, its graphematic representation is studied and the criteria used for the transcription of the Hebrew graphemes into Latin ones are described. The basis for the transcription was the Crónica Geral de Espanha (1344). Its data was handled through the computer program WordSmith Tools; in Chapter 3, the option for the semidiplomatic edition is justified, and the adopted norms of the transcription are described, before the presentation of the first 168 folios of De Magia; in Chapter 4, the graphemes bet, vet and vav are analyzed and compared between themselves and with the corresponding graphemes in the Latin and the non-aljamiado Old Portuguese. The interpretation of the data made it possible to conclude that three graphemes (bet, vet and vav) are being used instead of two ( and <v>) to represent the same sounds, bringing better understanding to the subject. The Appendix is composed of the transcription of some folios of the unedited manuscript 5-2-32, of the Colombina Library, in Sevilla, Spain, of some folios of the unedited manuscript Ms. Laud Or. 310, of the Bodleian Library, and the last folio of ms. 282. De Magia was the first aljamiado text in Portuguese edited and analyzed with strictness to explicit norms and attention to details. This pioneering study contributes to a more realistic phonic perspective of Old Portuguese and for a better comprehension of the codicological and paleographical aspects of medieval manuscripts. Hopefully, it will stimulate more studies of the Portuguese aljamias, kept unknown in library bookshelves.